Exploring Indonesia’s Taxation System, From Reforms To Its Impact On The Economy - Nenden Restu Hidayah; Karona Cahya Susena; Gioni Ogriansyah (Utami Publisher, 2025)
The taxation system is a vital component of Indonesia’s economic development. This article examines the journey of tax reforms in Indonesia, starting with the implementation of the Self-Assessment system in 1983 to the enactment of the Harmonized Tax Law (UU HPP) in 2021. These reforms aim to enhance state revenue, promote equity, and support sustainable development agendas, including the transition of a Carbon Tax. The impacts inclue an increase in the tax ratio, ease of doing business, income redisribution, and support for the green economy. Howener, challenges such as a low tax ratio and high non-compliance rates remain. This article highlights the importance of coninuous reforms to establish a fairer taxation system and support Indonesia’s inclusive and sustainable economic growth.